Disturbing Lipid Phase Equilibrium in Model Membrane Induced by Lytic Peptides - Alvares, Dayane S. [UNESP] (2022)
Lytic peptides are rich in cationic and hydrophobic residues that form amphipathic α-helix when in contact with lipid bilayers. Evidence showed that they act on the lipidic phase of the cell membranes, inserting into the lipid core and disturbing the lipid-packing. The insertion creates unbalanced elastic stresses in the outer and inner membrane leaflets that would be relieved by the opening of pores and/or defects and the consequent loss of the cell content. Here we compile results obtained in the investigations of the effects of three peptides on the lipid organization in model membranes whose compositions mimic the target plasma membrane of bacteria and cancer cells to which these peptides demonstrated lytic activity. These peptides have in their sequence the presence of both acidic and basic residues distributed such that they are third and fourth neighbors. We compiled results obtained from previous investigations with these peptides, using two main experimental techniques: lipid monolayers at the constant area and compression isotherms and differential scanning calorimetry. Here, we showed that the peptide-induced lipid packing perturbation was dependent on the structure of the polar head group and on the acyl chain.